MEASUREMENT OF SUSTAINABLE DEVELOPMENT IN LATVIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
Current paradigm of economic development is sustainable development. Sustainable development is the challenge for governments, companies and households because significant additional investments and innovations, changes in production and consumption habits are required. These changes have to be made because resources are limited and existence of our world is endangered – too much resources are used and too much waste is generated by people.  This problem is recognized by the United Nations that set 17 Goals of Sustainable Development in 2015. Review of scientific literature indicates that countries measure their sustainable development in different ways because countries have different development levels, as well as different social, economic and environmental problems. Thus the aim of this research is to identify Latvian approach measuring sustainable development and assess sustainable development in Latvia. Sustainable development in Latvia is measured by indicators defined in Sustainable Development Strategy in Latvia until 2030. The methods applied in this study are literature review and regression analysis. This study reveals Latvian progress in sustainable development and relationship among strategic indicators of sustainable development in Latvia.